2008
DOI: 10.1111/j.1600-0706.2008.16814.x
|View full text |Cite
|
Sign up to set email alerts
|

Oak seedling survival and growth along resource gradients in Mediterranean forests: implications for regeneration in current and future environmental scenarios

Abstract: Understanding seedling performance across resource gradients is crucial for defining the regeneration niche of plant species under current environmental conditions and for predicting potential changes under a global change scenario. A 2‐year field experiment was conducted to determine how seedling survival and growth of two evergreen and two deciduous Quercus species vary along gradients of light and soil properties in two Mediterranean forests with contrasting soils and climatic conditions. Half the seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 54 publications
7
52
0
1
Order By: Relevance
“…1D). A similar pattern of increasing mortality in higher light conditions has been found for oak seedlings in the Mediterranean [56] and linked to higher desiccation risk. Although several species followed this pattern, many others showed the opposite trend of decreasing mortality with increasing radiation, in agreement with many other studies linking light to survival (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…1D). A similar pattern of increasing mortality in higher light conditions has been found for oak seedlings in the Mediterranean [56] and linked to higher desiccation risk. Although several species followed this pattern, many others showed the opposite trend of decreasing mortality with increasing radiation, in agreement with many other studies linking light to survival (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…These include studies in which the light levels observed were all well below full sun exposure. Asymptotic models provide a satisfying parallel to the idealized photosynthetic response curve found in plant physiology textbooks, but our results and results from at least one other study (Gó mez-Aparicio et al 2008) suggest that a more complicated relationship may exist for saplings growing in the field. Additionally, although we know of no other study of R. cathartica sapling growth, our observations of growth response to light are consistent with two previous studies of R. cathartica seedling growth (Gourley 1985, Grubb et al 1996.…”
Section: Sapling Growth In Response To Resourcesmentioning
confidence: 54%
“…Oaks have gradually lost their ability to successfully regenerate in many European woodlands. This phenomenon is often referred to as ‘oak decline’ [29][31]. Available studies attribute it to various factors [32], [33], e.g.…”
Section: Introductionmentioning
confidence: 99%